Hubungan Metode Ceramah, Sikap Belajar, Strategi Mengajar Dosen Dan Status Ekonomi Dengan Indeks Prestasi Mahasiswa - Fitri, Dina Martha; Nurhidayah, Nurhidayah (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
Learning outcome is result of interaction acts and acts of teaching and learning.  Achievement is an attempt to know the mastery of course material by considering the knowledge, attitudes, and skills that reflect the students’ competence which results in an average value of learning outcomes that describe the levels of learning absorption of the students. The aim of this study is to determine the correlation among the lecture method, the learning attitude, the lecturer’s teaching strategies, and the family economic status towards the first semester achievement index of the second semester students in a study program of D-III Midwife in STIKes Medistra Indonesia. The design of this study is a quantitative research and method usedin this study is the method of Cross sectional analytic approach. To determine the number of samples, the researcher used Solvin formula, so that the sample obtained are 92 students.  The sampling technique used is stratified sampling random. Based on the result of the research, it can be concluded that the learning attitude, the lecturer’s teaching strategies, and the family economic status can affect the students’ achievement index. Suggestions for educational institutions are expected to be able to increase students' learning attitudes and to improve the lecturer’s teaching strategy in a way that can make the students be interested to study